Trade credit: the case of the agribusiness firms of the peruvian economy (1998-2013) - Cortez Cortez, Gaby (2014)
Trade credit is an operation of short-term credit linked to a commercial transaction in which the provider gives facilities to its customers for the purchase of their product under certain conditions to delaying payment.Trade credit plays an important role in agribusiness firms where coexist mainly small and medium producers of sugarcane and other recent complementary products (eg. Artichoke, bell pepper, grapes, etc), offering their products to companies with large scale of production and transformation of raw materials into refineries owned by these companies. These companies have access to financial sources and act as intermediary channels through commercial loans advance sums of money to small and medium farmers with a commitment to deliver their products. These relationships develop asymmetries where the market power held by some firms use trade credit as a major source of financing for producers with restricted access to credit markets. Current agribusinesses are located mostly on the Peruvian coast and are the result of land reform that affected the old haciendas, which were transformed by law 17716 in Agricultural Production Cooperatives, and later regulated by DL 802 they decided to change the cooperative model to limited companies.